NARKOBA DAN HUKUMAN MATI AKIBAT KORBAN PERDAGANGAN PEREMPUAN - Rosyid, Moh. (IAIN Pekalongan, 2015)
Narcotics are substances causing change of consciousness. Psychotropic is a substance that causes changes in mental activity and behaviour. There is negative impacts on its users. Surprisingly, the demand for narcotics is increasing. Some starts it as trial and error, to have fun, be used under certain conditions such as sadness, tense and disappointed, abuse / deviation and addicts. With the increasing demand, drug sellers attempt to increase their market in various ways including using women as couriers, although the death penalty confronting. The issue needs to be discussed further is the reasons these women becoming drug couriers. Data shows some women are trapped by drug sellers and they are victims of human trafficking promised to be married.Poverty is one factor of this problem. Thus, among the solutions is to fight against poverty by means of entrepreneurship education facilitated by government to become independent generation. Poverty is one of casualties in war against drug. Parents awareness to monitor and educate their children needs to be strengthen in order to prevent becoming targets of drugs' mafia, both becoming user or dealers. Meningkatnya animo konsumen, produsen terhadap narkotoka dan psikotropika, mengakibatkan mereka melakukan pemasaran dengan berbagai cara, antara lain, memanfaatkan perempuan menjadi pemasok/pengedar, meski hukuman mati menghadangnya. Persoalan yang perlu diurai adalah apa yang menjadi penyebab mau menjadi pengedar? Para perempuan yang menjadi pemasok/pengedar terjadi karena korban perdagangan manusia oleh oknum tertentu yang memanfaatkan celah kelemahan perempuan, yakni dinikah untuk dijadikan tumbal pengedar narkoba. Kemiskinan menjadi faktor penyebab menjadi korban. Dengan demikian, jalan awal yang harus dicari solusi adalah memerangi kemiskinan warga dengan cara pendidikan kewirausahaan agar menjadi generasi yang mandiri dan pemerintah memfasilitasinya. Bila kemiskinan masih akut, memerangi korban pengedar narkoba menghadapi jalan terjal. Perlunya kesadaran orangtua dalam mengawasi dan mendidik anaknya untuk dioptimalkan agar tidak menjadi target mafia narkoba, baik menjadi pengonsumsi, pengedar atau pemroduk narkoba. Ketegasan pemerintah dalam menindak kejahatan narkoba dengan hukuman mati yang prosedural jangan surut di tengah pro-kontra dari publik.